Integração energética da etapa de separação do solvente do processo de extração de óleo de soja - Cardoso, Ricardo (1999)
In this work it was undertaken a heat exchange network energetic adjustment of a soybean oil extraction plant. This plant belongs to the "Cooperativa Agropecuária Mouraoense" and is located at Campo Mourão city in the state of Paraná. In order to develop this work, it was carried out a field analysis to identify the heat exchange network of the crude oil extraction section, under continuous operation. This network was located more specifically in the sections of miscella distillation and hexane absorption. It was added to these equipment a cooler located in the outlet of the oil dryer. So, the network consisted of 2 heat exchangers, 1 heater and 7 coolers. Concepts and tools of a pinch analysis were used to treat data of the identified network. First, it was identified the low temperature difference (ΔΤmin) between the exchangers end streams of the network and this (ΔΤmin) it was determined the pinch point of the network. This was carried out by means of problem table algorithm procedure, wich also produced the goals for optimal hot and cold utilities consumption. Following, the actual network was represented in a grid diagram being identified a heater crossing the pinch point. The adjustment was carried out by using the pinch design method to relocate exchanger crossing the pinch point. In doing this the remaining energetic need was first supplied the crossing of process streams and only after supplied by utilities.. The propose network has a minimal number of units and presents no loops. As result this network consumes 85,71% of a hot utility and 2,38% of a cold utility less than the existent network.